Impact of donor site for bone graft harvesting for dental implants on health‐related and oral health‐related quality of life. Issue 6 (8th April 2012) - Reissmann, Daniel R.; Dietze, Björn; Vogeler, Michael; Schmelzeisen, Rainer; Heydecke, Guido
Abstract: Objectives: To assess and compare changes in health‐related quality of life (HRQoL) and oral health‐related quality of life (OHRQoL) after bone graft harvesting for dental implants with respect to the donor site. Material and methods: Autologous bone grafts were harvested in a consecutive sample of 23 patients (mean age: 46.1 years; 52% female) either from an intra‐oral (IO; N  = 8; chin, ascending ramus, buttress region) or an extra‐oral (EO; N  = 15; anterior iliac crest) donor site, followed by implant placements. HRQoL was self‐administered by the patients using the Short‐Form 36 (SF‐36) and OHRQoL was assessed using the Oral Health Impact Profile (OHIP‐49) preoperatively, 3 days and 4 weeks after surgery. Impact of donor site on changes in both concepts of QoL was determined in multiple linear regression analyses. Results: Patients with extra‐oral donor sites reported a substantial deterioration in the physical component (PC) of HRQoL indicated by an increase in the PC score of the SF‐36 ( P  < 0.001), whereas this score did not significantly change in patients with intra‐oral donor sites. The mental health component (MC) of HRQoL (MC score of the SF‐36) remained virtually identical in both groups. OHRQoL deteriorated from baseline (67.7 OHIP points) to first follow‐up (76.6 OHIP points) in both groups, however, changes were not statistically significant. Conclusion: In clinical decision‐making regarding donor site for bone graft harvesting, patients and clinicians should be aware of the expected decrease in HRQoL if deciding to use extra‐oral donor sites. Whenever possible, intra‐oral donor sites should be preferred.